2018
DOI: 10.1002/ijc.31785
|View full text |Cite
|
Sign up to set email alerts
|

An overview of 25 years of incidence, treatment and outcome of colorectal cancer patients

Abstract: Regarding the continuous changes in the diagnostic process and treatment of colorectal cancer (CRC), it is important to evaluate long‐term trends which are relevant in giving direction for further research and innovations in cancer patient care. The aim of this study was to analyze developments in incidence, treatment and survival for patients diagnosed with CRC in the Netherlands. For this population‐based retrospective cohort study, all patients diagnosed with CRC between 1989 and 2014 in the Netherlands wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
193
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(215 citation statements)
references
References 41 publications
8
193
2
Order By: Relevance
“…It appears that improvements in oncological treatments of any kind are the most likely explanations for the increased overall survival. However, the overall survival advantage for all patients is disappointing compared with for example colorectal cancer [23]. It is clear that improvements are needed, for instance through early detection of PDAC and better or individualised treatments [24].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that improvements in oncological treatments of any kind are the most likely explanations for the increased overall survival. However, the overall survival advantage for all patients is disappointing compared with for example colorectal cancer [23]. It is clear that improvements are needed, for instance through early detection of PDAC and better or individualised treatments [24].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year relative survival of mCRC increased from 4 to 12%, mainly due to intensified and more effective treatment. 3 Primary tumor location in CRC has prognostic value, suggesting that right-sided colon (RCC), left-sided colon (LCC), and rectal cancer can be regarded as different entities. Population-based studies found that patients with metastasized LCC had better survival compared with patients with metastasized RCC and demonstrated that in recent years patients with metastasized rectal cancer had a better survival than patients with metastasized colon cancer.…”
mentioning
confidence: 99%
“…Lifestyle factors, including smoking, diet, lack of exercise, combined with an aging population all contribute to an increased risk of CRC 39 . A number of advances have been made in recent years to both treatment and diagnosis; however, despite new treatments doubling survival for advanced disease 39 , prognosis for metastatic disease is still poor 40 . CRC frequently metastasizes to both the lungs and the liver, and this is a leading cause of treatment failure with up to 50% of CRC patients developing metastatic liver disease after resection of the primary tumour 41 .…”
Section: Discussionmentioning
confidence: 99%